Optimized neuropsychological procedures at different stages of dementia diagnostics - Damian, Marinella; Kreis, Markus; Krumm, Bertram; Hentschel, Frank (Journal of the neurological sciences, 2005)
Objective - To establish a staged procedure in dementia diagnostics and to propose specific, abbreviated test batteries suitable for the three diagnostic stages: Primary medical care, neuro-psychiatry, and memory clinic. - Methods - A total of 159 participants underwent comprehensive clinical, neurological, neuropsychological, and MRI examinations. The neuropsychological examination took approximately 90 min per individual and was based on tests of verbal and visual memory, language, abstract thinking, attention, visuo-constructive and spatial functions. Stepwise discriminant analyses were performed to identify which subset of the 18 variables of the comprehensive test battery was the most appropriate to differentiate between specific diagnostic groups, and which variables could be discarded to abbreviate the test battery without substantial loss in diagnostic accuracy. - Results - The abbreviated versions of the test battery retained adequate diagnostic accuracy. The accuracy decreased by maximally 4%, whereas the test administration time dropped substantially from previously 90 min to a maximum of 50 min. - Conclusion - Depending on the diagnostic question, a specifically abbreviated version of the comprehensive test battery can be used without unacceptably reducing diagnostic accuracy.